High levels of cerebrospinal fluid soluble triggering receptor expressed on myeloid cells 2 might be a biomarker of activity in pediatric patients with MOG-AD - Zhou, Anna; Zhang, Weihua; Ren, Changhong; Zhou, Ji; Chang, Haoxiao; Ren, Xiaotun (Frontiers in Pediatrics, 2022)
Myelin oligodendrocyte glycoprotein antibody disease (MOG-AD) is characterized by its monophasic or relapsing course and inflammatory demyelinating condition which is unable to be classified in typical multiple sclerosis (MS) or other known neuroinflammatory conditions. In the condition of neuroinflammatory, activated microglia is essential for demyelination. The secreted ectodomain of Triggering receptor expressed on myeloid cells 2 (sTREM2), expressed by microglial cells, is associated with abnormal biological pathway. It is known that the CSF sTREM2 concentration is much higher in neuroinflammatory and neurodegeneration diseases. However, the role of activated microglia has not been reported in MOG-AD pediatric patients. For the first time, the increased CSF and serum sTREM-2 concentration in pediatric patients with MOG-AD is investigated in this work, showing evidence of microglia activation in MOG-AD. CSF sTREM2 levels significantly correlated with clinical inflammatory indexes and adapted modified Rankin scale score, indicating the potential value of sTREM2 as a severity biomarker.